(untitled) - Yuan, J. S. (New York, 1998)
This book provides comprehensive coverage of device simulation and analysis for various modem semiconductor devices. It will serve as a reference for researchers, engineers, and students who require in-depth, up-to-date information and understanding of semiconductor device physics and characteristics. The materials of the book are limited to conventional and mainstream semiconductor devices; photonic devices such as light emitting and laser diodes are not included, nor does the book cover device modeling, device fabrication, and circuit applications.
Mô phỏng linh kiện bán dẫn
Keywords: Semiconductors,Chất bán dẫn; Computer simulation.,Mô phỏng máy tính